Development, characterization and in vivo zinc absorption capacity of a novel soy meal hydrolysate-zinc complexes - Wang, Rongxin; Ye, Meijun; Zhu, Suyin; Zeng, Qingzhu; Yuan, Yang (Frontiers in Nutrition, 2023)
BACKGROUND: Zinc is an essential trace element for the human body. Recently, a novel Zn-binding peptide, Lys-Tyr-Lys-Arg-Gln-Arg-Trp (PP), was purified and identified from soy protein hydrolysates with high Zn-binding capacity (83.21 ±2.65%) by our previous study. The preparation of soy meal hydrolysates (SMHs)-Zn complexes is convenient and low-cost, while PP (Lys−Tyr−Lys−Arg−Gln−Arg−Trp)-Zn complexes have a higher coordination rate but a relatively high cost. The aim of this study was to investigate the effect of soy meal hydrolysates (SMHs)-Zn complexes on zinc absorption in mice model, and synthetic soy peptide (PP)-Zn complexes with high Zn-binding capacity were used as control. Firstly, SMHs were prepared by enzymolysis, and the PP (Lys−Tyr−Lys−Arg−Gln−Arg−Trp) were synthesized based on previous studies. The binding mechanism of soy hydrolysates and zinc was analyzed by spectral analysis. Furthermore, the cytotoxicity of the SMHs-Zn complexes was also studied using the CCK-8 method. The effect of zinc absorption was evaluated based on Zn content, total protein and albumin content, relevant enzyme system, and the PeT1 and ZnT1 mRNA expression levels. RESULT: The result showed that zinc was bound with carboxyl oxygen and amino nitrogen atoms on SMHs, with hydrophobic and electrostatic interactions as auxiliary stabilizing forces. SMHs-Zn were proved to have great solubility and a small particle size at different pH values, and it showed a beneficial effect on Caco-2 cells growth. Moreover, it was proved that SMHs-Zn and PP-Zn could increase the levels of zinc and the activity of Zn-related enzymes in mice. SMHs-Zn possessed higher PepT1 and ZnT1 mRNA expression levels than PP-Zn in the small intestine. CONCLUSION: SMHs-Zn with a lower Zn-binding capacity had similar effects on zinc absorption in mice as PP-Zn, suggesting that the bioavailability of peptide-zinc complexes in mice was not completely dependent on their Zn-binding capacity, but may also be related to the amino acid composition.